Кон Lois McNay, Foucault and Feminism: Power, Gender and the Self: Për Lois McNay, Foucault and Feminism: Power, Gender and the Self - Sekulovski, Jordančo; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Jordančo Sekulovski | Јорданчо Секуловски Title (Macedonian): Кон Lois McNay, Foucault and Feminism: Power, Gender and the Self Title (Albanian): Për Lois McNay, Foucault and Feminism: Power, Gender and the Self Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 293-295 Page Count: 3 Citation (Macedonian): Јорданчо Секуловски, „Кон Lois McNay, Foucault and Feminism: Power, Gender and the Self“, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 293-295. Citation (Albanian): Jordančo Sekulovski, „Për Lois McNay, Foucault and Feminism: Power, Gender and the Self“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 293-295.